Kinerja Kepala Sekolah dan Guru dalam Mengimplementasikan Pendidikan Inklusif - Munawir Yusuf (Jurnal Pendidikan dan Kebudayaan, 2012)
This study aimed to describe the performance of school principals and teachers inimplementing inclusive education in primary school. To achieve these objectives, a research survey has been conducted at primary schools that organize inclusive education in 4 area districts, namely Surakarta, Karanganyar, Sukoharjo and Boyolali, in Central Java Province. The numbers of samples in this study were 51 inclusion elementary schools, 51 school principals, and 103 classroom teachers. Data were collected and processed using questionnaires and descriptive statistics, respectively. Questionnaire Validity for School Principals is in the range of 0312-0796 with 0962 reliability. Questionnaire Validity for Teachers is in the range of 0290-0815 with 0956 reliability. The results can be summarized as follows: 1) The performance of school principals in implementing inclusive education is in the medium category; 2) performance of classroom teachers in implementing inclusive education is in the medium category; and 3)Principal performance score average (65.45 %), higher than the average score achieved by teachers (62.3%).ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan kinerja kepala sekolah dan guru dalam mengimplementasikan pendidikan inklusif di sekolah dasar (SD). Untuk mencapai tujuan tersebut, dilakukan penelitian survei ke SD penyelenggara pendidikan inklusif di 4 (empat) wilayah kabupaten/kota, yaitu Surakarta, Karanganyar, Sukoharjo, dan Boyolali, Provinsi Jawa Tengah. Jumlah sampel dalam penelitian ini 51 SD Inklusi, 51 kepala sekolah, dan 103 guru kelas. Data dikumpulkan dengan menggunakan angket dan diolah secara statistik deskriptif. Validitas angket kepala sekolah berada dalam rentang 0.312 - 0.796 dengan reliabilitas 0.962. Validitas angket guru berada dalam rentang 0.290 - 0.815 dengan reliabilitas 0.956. Hasil penelitian menunjukkan bahwa: 1) kinerja kepala sekolah dalam mengimplementasikan pendidikan inklusif berada dalam kategori sedang; 2) kinerja guru kelas dalam mengimplementasikan pendidikan inklusif berada dalam kategori sedang; dan 3) skor kinerja kepala sekolah rata-rata (65,45%), lebih tinggi dibanding skor rata-rata yang dicapai guru (62,3%).